Peningkatan Hasil Belajar Siswa dengan Menggunakan Media Video pada Pembelajaran Tematik Terpadu di Kelas V SD - Putri, Silvi Rahma; Lena, Mai Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This study aims to describe the increase in student learning outcomes in integrated thematic learning using video media in Class VB SDN 09 Sungai Limau, Padang Pariaman Regency. The research conducted was a type of PTK using qualitative and quantitative approaches. The results obtained showed an increase in: a) The assessment of the learning implementation plan in cycle I was 86.10%, in cycle II there was an increase of 91.66%. b) Assessment of teacher activity cycle I obtained 82.14%, in cycle II increased to 92.85%. c) Assessment of student activities in cycle I 82.14%, in cycle II has increased to 92.85%. Assessment of student learning outcomes in cycle I obtained an average value of 71.28 and increased in cycle II to 85.28.